Quasi-static motion of compressible hypo-elastic sphere and cylinder - ZHONG-HENG, Guo; WEN-LIN, Lii (Engineering Transactions, 1980)
The present paper deals with the quasi-static motion of compressible hypo-elastic bodies of grade zero and grade one, The initial-boundary problems of the raidal motion of a sphere and the plane-radial motior of a cylinder have been studied in detail, their exact solutions being obtained. It has been concluded that for any fixed moment the density of mass and the stress field of the body are homogeneous, while the velocity of the particle is in proportion to its distance from the centre of the sphere (or, from the axis of the cylinder).